2012
DOI: 10.7439/ijpc.v2i1.420
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Atorvastatin Calcium and Telmisartan in Pharmaceutical Formulations by Reverse Phase-High Performance Liquid Chromatography

Abstract: ABSTRACT:A simple, sensitive and reproducible reverse-phase high performance liquid chromatographic (RP-HPLC) method has been developed for simultaneous quantitative estimation of Atorvastatin calcium (ATOR) and Telmisartan (TELM) in the pharmaceutical formulations. Chromatographic separation was achieved on a 250 × 4.6 mm, 5µ, Waters symmetry column. The flow rate was 1ml/min and eluent was monitored by absorbance at 267 nm using a mixture of Methanol and Acetonitrile (pH 3.0±0.01) in the ratio of 25:75 (v/v)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The literature data have shown that atorvastatin, like most of the statins, is a very unstable molecule and the analytical processing of this active ingredient is still a current problem. Also, reviewed literature data include only a few studies, where the instability of atorvastatin in hydrolytic, oxidative or photolytic condition was mentioned as a part of the selectivity of the stability-indicating methods [18][19][20][21][22][23][24][25][26][27][28][29][30]. To date, to the best of our knowledge, none of the reported analytical procedures describe a simple and satisfactory sample preparation methodology where the influence of the stressor straight, time of expose and temperature are evaluated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The literature data have shown that atorvastatin, like most of the statins, is a very unstable molecule and the analytical processing of this active ingredient is still a current problem. Also, reviewed literature data include only a few studies, where the instability of atorvastatin in hydrolytic, oxidative or photolytic condition was mentioned as a part of the selectivity of the stability-indicating methods [18][19][20][21][22][23][24][25][26][27][28][29][30]. To date, to the best of our knowledge, none of the reported analytical procedures describe a simple and satisfactory sample preparation methodology where the influence of the stressor straight, time of expose and temperature are evaluated in detail.…”
Section: Introductionmentioning
confidence: 99%